Pengaruh Disiplin Kerja dan Pengawasan Terhadap Produktivitas Kerja Bagian Sewing Pada PT. Horn Ming Indonesia, Tangerang - Puji Wulan Sari; Mudhita Elviani; Jaka Slameta (Universitas Tangerang Raya, 2023)
The purpose of this study was to determine the effect of work discipline and supervision on work productivity in the sewing department at PT Horn Ming Indonesia, Tangerang. The research method was conducted with quantitative method and the analysis method used in this research is multiple regression analysis. The population of this study is PT Horn Ming Indonesia, Tangerang which consists of 5 lines and all employees amounted to 167 employees. The sampling technique used purposive sampling technique method and sample calculation with slovin formula so that the number of respondents was 118 employees. The results showed that partially there is a significant influence between work discipline (X1) on work productivity (Y) and and partially there is a significant influence between supervision (X2) on work productivity (Y) and there is a significant influence between the variables of Work Discipline (X1) and Supervision (X2) on the work productivity of the sewing section at PT. Horn Ming Tangerang, Indonesia (Y) and the results of this study are expected from the leadership of PT. Horn Ming Indonesia, Tangerang to pay more attention to work discipline and supervision because it can support employee work productivity.